Pengembangan Media Kuartet Suku Dan Agama “Sukma” Di Indonesia Muatan Ips Kelas IV SD Negeri 13 Gelumbang - Tarisa Yulianti; Aryaningrum, M.Pd; Hetilaniar, M.Pd (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This development research aims to produce a valid, practical and effective media quartet of tribes and religions "SUKMA" in Indonesia for grade IV elementary school. This study uses development research or research and development. In this study the number of subjects was 20 students. This media was developed using the ADDIE model which includes 5 stages namely analyze, design, develovment, implementation, and evaluate. Data collection was done by interview, validation questionnaire, and student response questionnaire. This research produced a quartet of ethnic and religious media "SUKMA" in Indonesia which is a learning media in the form of printed media. The results of data analysis of the development of tribal and religious quartet media "SUKMA" in Indonesia social studies content conducted and developed by researchers categorized as very valid seen from the validation questionnaire sheet with an average of 87.5%, tribal and religious quartet media "SUKMA" in Indonesia social studies content developed categorized as very practical seen from the questionnaire sheet One to One with an average value of 90.5% and small group in the trial with an average value of 93%. Media quartet of tribes and religions "SUKMA" in Indonesia social studies content developed is categorized as effective with an average value of 79.5%. Based on the results of validation and trials as well as potential effects, it is concluded that the tribal and religious quartet media "SUKMA" in Indonesia social studies content is suitable for use in the learning process. Keywords: Tribal and Religious Quartet Media, SUKMA, and Social Studies.